Morphological and Rheological Guided Design for the Microencapsulation Process of Lactobacillus paracasei CBA L74 in Calcium Alginate Microspheres - Di Natale, Concetta; Lagreca, Elena; Panzetta, Valeria; Gallo, Marianna; Passannanti, Francesca; Vitale, Michele; Fusco, Sabato; Vecchione, Raffaele; Nigro, Roberto; Netti, Paolo (Frontiers in Bioengineering and Biotechnology, 2021)
The intestinal microbiota is a real ecosystem composed of several bacterial species and a very huge amount of strains that through their metabolic activities play a crucial role in the development and performance of the immune system and other functions. Microbiota modulation by probiotics establishes a new era into the pharmaceutical and healthcare market. Probiotics play, in fact, an important role in helping and sustaining human health but, in order to produce benefits, their viability must be preserved throughout the production process up to consumption, and in addition, their bioactivity required to be safeguarded while passing through the gastrointestinal tract. In this frame, encouraging results come from encapsulation strategies that have proved to be very promising in protecting bacteria and their viability. However, specific effort has to be dedicated to the design optimization of the encapsulation process and, in particular, to the processing parameters that affect capsules microstructure. Herein, focusing on calcium alginate microspheres, after a preliminary selection of their processing conditions based on size distribution, we implemented a micro-rheological analysis, by using the multiple-particle tracking technique, to correlate the inner microstructure to the selected process conditions and to the viability of the Lactobacillus paracasei CBA L74. It was assessed that the explored levels of cross-linking, although changing the microorganism constriction, did not affect its viability. The obtained results confirm how this technology is a promising and a valid strategy to protect the microorganism viability and ensure its stability during the production process.